A surprising complete response to cadonilimab in a primary metastatic cervical cancer: a case report - Yu, Haijuan; Lin, Jie; Chen, Jian; Chen, Lijun; Zou, Jianping; Liu, Bin; Hu, Dan; Xiao, Youping; Yu, Linhao; Sun, Yang (Frontiers in Immunology, 2024)
The outcome of patients with recurrent/metastatic cervical cancer (R/M CC) is poor, with a 5-year survival rate of only 10%–20%. Recent advances in immunotherapy renewed its interest in R/M CC treatment. It has been suggested that cadonilimab, a novel bispecific antibody targeting programmed death 1 (PD-1) and cytotoxic T-lymphocyte antigen-4 (CTLA-4), significantly improved the survival outcomes of the R/M CC. In the present study, we reported a programmed death ligand 1 (PD-L1) and human epidermal growth factor receptor 2 (HER-2) positive CC case at stage IV who was treated with cadonilimab and achieved a surprising radiographic complete response (CR) for 10 months, even in the PD-L1 negative metastatic site. Demographic, clinical, histopathological, laboratory, treatment regime and imaging data were recorded. Unfortunately, the patient progressed rapidly during maintenance therapy when cadonilimab was replaced by sintilimab, the monoclonal antibody against PD-1, indicating the more powerful anti-tumor activity of dual blockade immunotherapy. To conclude, cadonilimab offers a promising and effective therapeutic approach for R/M CC. Notably, HER-2 is also expected to be a new reference target for cadonilimab therapy.